The impact of virtual simulation technology and blended learning methods on nursing students' performance, acceptance and transition to clinical practice in higher vocational education - Liu, Dan; Anyanwu, Clinton Chidiebere; Liu, Yaoping (Journal of Asian Scientific Research, 2025)
In the context of China's national vocational education digitalization framework, nursing education virtual simulation (VS) is still not fully utilized as a resource to link theory and practice. The objective of this study is to compare the effects of VS-based blended learning (VS-BL) and traditional blended learning (T-BL) on nursing students’ knowledge, skills, acceptance, and clinical readiness. A quasi-experimental design was employed with a sample of 79 vocational nursing students. The VS-BL group (n = 39) was exposed to a formal simulation unit prior to practical skills performance, while the T-BL group (n = 40) received traditional training. Theoretical scores (M = 86.33 ± 8.18) and OSCE performance (M = 84.38 ± 2.68) were significantly higher in the VS-BL participants than in the T-BL group (p < 0.001). Additionally, the percentage of VS-BL students who felt prepared for clinical experience, self-directed learning, or professional identity development increased by 84.6%. The findings indicate that incorporating virtual simulation within blended learning significantly enhances students’ competencies and preparedness for clinical practice, highlighting its potential as an effective educational resource in nursing training.